Evaluation of histopathology examination of routine tonsillectomy and adenoidectomy specimens in developing countries (2011)
Objective: Healthcare costs are usually borne directly by patients or relations in developing countries; therefore reducing waste in the system is very important. This study aims to determine the necessity of full histopathology examination in routine tonsillectomy and adenoidectomy in children. Methods: A retrospective chart review of patients 18 years and younger who underwent tonsillectomy and/or adenoidectomy between January 1986 and December 2006 at the University College Hospital, Ibadan, Nigeria was done. The age, sex, surgical procedure and pathology results were recorded. Histology reports were broadly classified into: non-neoplastic and neoplastic pathologies. Charts of neoplastic pathologies were pulled and the medical history reviewed. Results: A total of 244 patients met the inclusion criteria with a mean age of 5.3 ±4.7 years. There were 150 males (61.5%) and 94 females (38.5%). Tonsillectomy and adenoidectomy were performed together on 74 patients (30.3%) while tonsillectomy and adenoidectomy alone were performed on 60 (24.6%) and 110 (44.7%) patients, respectively. Review of the pathology reports revealed two cases of malignancies with an incidence of 0.82%. Conclusion: Medico-legal factors will suggest the review of all surgical specimens. Therefore it is important to identify innovative approaches to reduce costs of histopathology examination in routine tonsillectomies and adenoidectomies